1968
DOI: 10.1172/jci105940
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and calcium kinetic studies in idiopathic hypercalciuria

Abstract: A B S T R A C T Calcium balances and calcium kinetic studies using 47Ca were performed in nine male patients with idiopathic hypercalciuria and in three normal male subjects. A sharp reduction in calcium intake in eight patients with idiopathic hypercalciuria caused a decrease in urinary calcium excretion, the latter remaining elevated above that reported for normal subjects on a low calcium diet. The hypercalciuric patients had an enlarged miscible calcium pool size, an increased calcium turnover rate, increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
1

Year Published

1973
1973
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 30 publications
1
34
1
Order By: Relevance
“…Studies using radio-labeled calcium that have compared intestinal calcium absorption in patients with IH to that in normal subjects find consistently increased calcium uptake in IH ( Figure 1, panel a) [9;10]. Although not measured in these studies, other work has shown that gut calcium secretion is not altered in subjects with IH, meaning that net absorption is also increased [11]. Absorption is higher in IH at all levels of calcium intake [12], and reflects an increase in active calcium transport by the intestine.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Studies using radio-labeled calcium that have compared intestinal calcium absorption in patients with IH to that in normal subjects find consistently increased calcium uptake in IH ( Figure 1, panel a) [9;10]. Although not measured in these studies, other work has shown that gut calcium secretion is not altered in subjects with IH, meaning that net absorption is also increased [11]. Absorption is higher in IH at all levels of calcium intake [12], and reflects an increase in active calcium transport by the intestine.…”
mentioning
confidence: 76%
“…Overall, it appears that renal mineral conservation must be abnormal in IH, and bone mineral loss somehow facilitated so that despite the absence of diet calcium to balance renal losses, serum calcium can remain normal and serum PTH suppressed. This is further suggested by studies of calcium kinetics using 47 Ca which demonstrate a larger exchangeable calcium pool and higher calcium turnover, together with increased rates of both bone formation and resorption, in 9 subjects with IH compared to 3 normal subjects [11].A possible mechanism that could explain bone mineral lability and abnormal renal tubule conservation of calcium, as well as increased gut absorption of calcium, would be altered tissue …”
mentioning
confidence: 94%
“…Since a is high in absorptive hypercalciuria, one would expect EFC or net secreted Ca to be lower than in the control group. In the study of Liberman et al (27). EFC varied from 31 mg to 178 mg/day with a mean value of 99 mg/day among patients with idiopathic hypercalciuria.…”
Section: Discussionmentioning
confidence: 98%
“…Although the value of CaA -Cauv of + 49±27 SD mg/day was less than in the control group, it may have still reflected the net secreted calcium. The endogenous fecal calcium (EFC) has been shown to be inversely related to the fractional Ca absorption (26,27), and directly related to calcium intake (26). Since a is high in absorptive hypercalciuria, one would expect EFC or net secreted Ca to be lower than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, both defects might contribute to explain bone mass in HSFs (7,19). These characteristics of strontium handling suggest that HSFs could represent a specific group of hypercalciuric patients having a disorder of cellular calcium transport predisposing to hypercalciuria, stone production, and low bone mass.…”
Section: Discussionmentioning
confidence: 99%